Diagnostic Testing in Central Nervous System Infection - Kanjilal, Sanjat; Cho, Tracey A.; Piantadosi, Anne (Seminars in Neurology, 2019)
Patients with central nervous system (CNS) infection experience very high levels of morbidity and mortality, in part because of the many challenges inherent to the diagnosis of CNS infection and identification of a causative pathogen. The clinical presentation of CNS infection is nonspecific, so clinicians must often order and interpret many diagnostic tests in parallel. This can be a daunting task given the large number of potential pathogens and the availability of different testing modalities. Here, we review traditional diagnostic techniques including Gram stain and culture, serology, and polymerase chain reaction (PCR). We highlight which of these are recommended for the pathogens most commonly tested among U.S. patients with suspected CNS infection. Finally, we describe the newer broad-range diagnostic approaches, multiplex PCR and metagenomic sequencing, which are increasingly used in clinical practice.
Keywords: meningitis; encephalitis; diagnostic; metagenomic sequencing